Hierarki Ranah Pembelajaran Afektif Pendidikan Agama Islam dalam Perspektif Taksonomi Qur'ani - Suliswiyadi, Suliswiyadi (Universitas Muhammadiyah Magelang, 2020)
The unsuccessful factors of religious education practice that are often found in schools regarding the achievement of student learning outcomes are assumed to focus more on aspects of cognitive abilities rather than the growth of religious awareness, neglect of the touch of affective aspects development, adoption of Bloom's cognitive-taxative affective domain practices. This study aims to uncover the epistemological point of view that discusses the problems of the concept of scientific theory in aspects of learning the perspective of the Qur'an. The contribution of the results of the study or novelty of this finding is beneficial for the practice of Islamic religious education learning in order to develop an affective domain according to the concepts of the Koran. The study method used